Invasive Plant Ecology and Management: Linking Processes to Practice - Monaco, Thomas A (CABI, 2014)
h e primary objective of this book is to illustrate how understanding ecological processes will foster scientii cally based approaches to invasive plant management in semi-arid ecosys- tems. Ecological processes serve as the underpinning and common ground within the scien- tii c literature that bridges the gap between researchers and land managers. Our focus on ecological processes is also justii ed based on the overwhelming realization that invasive plant management must move beyond treating symptoms of damaged lands to repairing and inl uencing the processes responsible for plant community change. While our emphasis is clearly slanted towards semi-arid wildlands, we believe the ecological principles outlined by the contributing authors can easily be applied to many other systems impacted by inva- sive plant species. Assessing ecological processes and how they are impacted by invasive plant species is a critical aspect of land management, which can easily be overlooked when the impetus to “do something” overshadows sound decision-making. Part 1 of this book, comprising Chapters 1 through 5, provides a compelling justii cation to assess ecosystem and landscape heteroge- neity and historical land-use legacy ef ects before a process-based understanding of how ecosystems operate can be realized. In this same vein, Part 1 also showcases how the emerg- ing concept of resource pool dynamics provides a much more adequate mechanism to assess ecological processes associated with plant resource use than traditional emphasis on compe- tition. Concluding Part 1 with a comprehensive assessment of how invasive species impact soils, nutrient cycling, and microbial communities emphasizes that ef ective invasive plant management will also require designing management practices that inl uence processes that operate within soils.